Spectrum of Histopathological Findings of Gall Bladder Diseases at A Tertiary Level Hospital of Nepal - Bhandari, Anita; Bagale, Bishow Bandhu (Journal of College of Medical Sciences-Nepal, 2025)
Background Gallbladder diseases are a significant cause of morbidity, with chronic cholecystitis being the most prevalent histopathological diagnosis. This study highlighted the importance of routine histopathological evaluation of the gallbladder specimens while assessing the histopathological spectrum of gallbladder diseases in patients undergoing cholecystectomy at Bharatpur Hospital, Nepal.MethodsAn observational study was conducted including 200 gallbladder specimens from patients who underwent cholecystectomy between March 2022 and March 2023 at Bharatpur hospital, Chitwan, Nepal. Specimens were processed using standard histopathological techniques, including fixation in 10% formalin and Hematoxylin & Eosin staining. Data were processed in Microsoft Excel and analyzed using Stata/BE version 18.0. ResultsThe participants in the study aged between 8 to 78 years with mean age 41.87 ± 14.36. Among them 158 participants were females (79%) and 42 were males (21%). Chronic cholecystitis was the most common diagnosis (74.5%), observed in 115 females (73.0%) and 34 males (81.0%). Chronic cholecystitis with Cholesterolosis was noted in 20% of cases, more frequent in females (20.9%) than males (16.7%). Rare findings, including adenomyosis, pyloric metaplasia, and intestinal metaplasia, were predominantly observed in females.Conclusions Chronic cholecystitis, either alone or with associated features, was the predominant histopathological diagnosis in this study. However, routine histopathological evaluation of gallbladder specimens should be carried out to ensure appropriate diagnosis of pathological conditions associated with gallbladder.